Obstetric Emergencies: Feto-maternal Outcome at a Teaching Hospital - Saha, R; Gautam, P (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to know the pattern of obstetric emergencies and its influence on maternal and fetal outcome. Methods: A descriptive study was carried out in the department of obstetrics and gynecology at Kathmandu Medical College Teaching Hospital from 1st June 2013 to 31st May 2014. Cases were categorized as early pregnancy emergencies (ruptured ectopic pregnancy, complications of abortion), ante-partum emergencies and intra-partum emergencies (antepartum haemorrhage, preeclampsia, eclampsia, preterm prelabor rupture of membranes, rupture uterus), post-partum emergencies (postpartum haemorrhage, retained placenta, placenta accreta, uterine inversion), puerperal emergencies (postpartum sepsis), fetal emergencies (cord prolapse, shoulder dystocia). Outcome noted were type of emergency, obstetric intervention done, maternal and perinatal morbidity and mortality. Results: A total of 80 (4.45%) obstetric emergencies occurred among 1796 deliveries .The most common obstetric emergencies were obstetric hemorrhage (62.5%), severe preeclampsia (23.5%) and preterm prelabor rupture of membranes (10%). The obstetric interventions done were cesarean section (43.75%), exploratory laparotomy (33.75%) and blood transfusion (40%). Obstetric emergencies were responsible for 66.6% of total maternal death and 24.56% of total perinatal death. Conclusions: In spite of best efforts, some obstetric emergencies do occur. Obstetric hemorrhage and severe preeclampsia are the frequent obstetric emergencies. Cesarean section, exploratory laparotomy and blood transfusion were the commonly performed interventions. A better outcome can be achieved by national policy of promoting utilization of antenatal care, institutional deliveries, skilled birth attendance at delivery, liberal blood transfusion and regular training of doctors and nurses. DOI: http://dx.doi.org/10.3126/njog.v9i1.11186 NJOG 2014 Jan-Jun; 2(1):37-40